2006
DOI: 10.1021/es061438n
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation and Mathematical Modeling of Microbially Enhanced Tetrachloroethene (PCE) Dissolution

Abstract: Experiments to assess metabolic reductive dechlorination (chlororespiration) at high concentration levels consistent with the presence of free-phase tetrachloroethene (PCE) were performed using three PCE-to-cis-1,2-dichloroethene (cis-DCE) dechlorinating pure cultures (Sulfurospirillum multivorans, Desulfuromonas michiganensis strain BB1, and Geobacter lovleyi strain SZ) and Desulfitobacterium sp. strain Viet1, a PCE-to-trichloroethene (TCE) dechlorinating isolate. Despite recent evidence suggesting bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 53 publications
2
103
1
Order By: Relevance
“…Cultures of Desulfitobacterium sp. strain Viet1, a PCE-to-TCE dechlorinator [32], were used to determine the typical magnitude of primary and secondary chlorine isotope effects. Further, cultures of Geobacter lovleyi strain SZ, a PCE/TCE-to-cis-DCE dechlorinator [33], were used to specifically investigate whether one or two C-Cl bonds are reactive in TCE as non-symmetric molecule.…”
Section: Scheme 2 Proposed Degradation Pathways Of Tce Catalyzed By mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures of Desulfitobacterium sp. strain Viet1, a PCE-to-TCE dechlorinator [32], were used to determine the typical magnitude of primary and secondary chlorine isotope effects. Further, cultures of Geobacter lovleyi strain SZ, a PCE/TCE-to-cis-DCE dechlorinator [33], were used to specifically investigate whether one or two C-Cl bonds are reactive in TCE as non-symmetric molecule.…”
Section: Scheme 2 Proposed Degradation Pathways Of Tce Catalyzed By mentioning
confidence: 99%
“…In the compound-average chlorine ε PCE of the PCE experiment, the primary isotope effect in the reacting C-Cl bond is "diluted" with three secondary isotope effects according to Equation (32). In the TCE experiment, only two secondary isotope effects contribute so that the primary isotope effect is more strongly represented in ε TCE,chlorine .…”
mentioning
confidence: 99%
“…and down. In this part the absence of Dhb and Dhc could be due to high concentrations levels of chlorinated ethenes that can have an inhibiting or toxic effect to the bacteria (Amos et al, 2007;Duhamel et al, 2002;Sabalowsky and Semprini, 2010).…”
Section: Degradation Of Tce To Cis-dce At High Concentrations In the mentioning
confidence: 99%
“…4). This is not surprising, as others have shown that the build up of toxic dechlorination products during enrichment and extended exposure to saturation concentrations of TCE inhibit the growth of Dehalococcoides mccartyi strains (25)(26)(27).…”
Section: Figmentioning
confidence: 72%